Particles as hedges - Fitriana, Irta; Sari, Hidayatul Anggun (Pioneer: Journal of Language and Literature; Vol 18 No 1 (2026)DO - 10.36841/pioneer.v18i1.6950, 2026)
This study investigates Luffy’s use of Hedges Encoded in Particles (HEPs) as negative politeness strategies based on Brown and Levinson’s framework. It examines their use in recruitment interactions to express intentions while minimizing imposition and avoiding threats to the interlocutor’s negative face. Focusing specifically on recruitment contexts, the study analyzes how Luffy invites others to join his crew without pressure or coercion, thereby clarifying the pragmatic function of HEPs and avoiding overlapping interpretations of politeness strategies. Using a descriptive qualitative design, the data were collected through systematic transcription and note-taking of Luffy’s utterances across eight episodes of the series, with particle-based hedges as the unit of analysis. The findings identify 47 instances in which HEPs are used to mitigate face-threatening acts and maintain a polite, non-imposing tone, particularly in interactions with potential crew members. These particles function as hedging devices that soften illocutionary force and signal respect for the interlocutor’s autonomy. Rather than serving merely as discourse fillers, HEPs operate as pragmatic resources that shape interpersonal meaning and interactional alignment. This study contributes to pragmatic research by highlighting the functional role of particles in negative politeness strategies and by extending politeness analysis to character-driven media discourse, especially within live-action adaptations.